Phase-transition-induced dynamic surface wrinkle pattern on gradient photo-crosslinking liquid crystal elastomer - Tao Wen; Tianjiao Ma; Jie Qian; Zhaoxin Song; Xuesong Jiang; Yuan Yao (Nature Communications)
Abstract Liquid crystal elastomers (LCEs) with various deformation properties based on phase transition were widely used as actuators and provided potential to fabricate functional surfaces with tunable microstructure. Herein, we demonstrate a strategy to fabricate dynamic micro wrinkles on LCE surfaces based on LC phase transition. Stable micron-sized surface wrinkles on the anthracene-containing LCE film (AnLCE) are fabricated by ultraviolet exposure induced gradient cross-linking and subsequently stretching-releasing (UV-SR). The surface wrinkle is stabilized by the orientation of liquid crystal mesogens in the crosslinked top layer, while it can be erased by heating due to the isotropic phase-transition and recovered by stretching-releasing again. The dynamic natures cooperated with multi display modes under natural light, UV light and polarized light enable wrinkled AnLCE as a dynamic and multi-mode display platform. This strategy provide a path for modifying LCEs and regulating surface polarized images via wrinkling, which may be potential in soft sensors and optics, smart windows and anti-counterfeiting.